KEDUDUKAN INFORMED CONSENT PADA PELAYANAN PASIEN DI RUMAH SAKIT - Dr. Redyanto Sidi (Universitas Labuhanbatu, 2020)
In this informed consent, many patients do not know the extent of their rights as recipients of health services, and hospitals and doctors as health service providers are obliged to carry out their obligations for the benefit of patients. As a patient should also accept the advice given by the doctor. The relationship between doctor and patient arises when the patient first comes with the intention of seeking help. From that moment on, what is meant by Informed Consent, namely the arrival of a patient, which means he has given confidence to the doctor, automatically implants an attitude that aims to prioritize the health of his patient. The relationship between the doctor and the patient is a special bond, but the patient has the right to decide whether or not the doctor may continue the relationship. It depends on what information the patient gets about the doctor's actions.In the legal aspect, informed consent is regulated in Law No. 29 of 2004 concerning medical practice, which states that